2012
DOI: 10.1007/978-94-007-2663-5
|View full text |Cite
|
Sign up to set email alerts
|

Lighter than Air Robots

Abstract: No part of this work may be reproduced, stored in a retrieval system, or transmitted in any form or by any means, electronic, mechanical, photocopying, microfilming, recording or otherwise, without written permission from the Publisher, with the exception of any material supplied specifically for the purpose of being entered and executed on a computer system, for exclusive use by the purchaser of the work.Cover design: VTeX UAB, Lithuania

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 135 publications
(217 reference statements)
0
5
0
Order By: Relevance
“…In the search for airship autonomy, it is fundamental to assure good positioning and path-tracking features for the control and guidance (CG) framework. In our case, the proposed architecture for the CG system encompasses four components: path planning, guidance, control and data acquisition [5,7]. The path planner generates the trajectory reference for the guidance loop, which tries to minimize the pose (position/orientation) error, while the control level tracks the velocity and acceleration commands.…”
Section: Control and Guidance Proposalmentioning
confidence: 99%
See 1 more Smart Citation
“…In the search for airship autonomy, it is fundamental to assure good positioning and path-tracking features for the control and guidance (CG) framework. In our case, the proposed architecture for the CG system encompasses four components: path planning, guidance, control and data acquisition [5,7]. The path planner generates the trajectory reference for the guidance loop, which tries to minimize the pose (position/orientation) error, while the control level tracks the velocity and acceleration commands.…”
Section: Control and Guidance Proposalmentioning
confidence: 99%
“…However, in both cases, robust flight under actual weather conditions is still one of the biggest issues that prevent airships from fully realizing maneuverability advantages. In this way, safe and accurate airship control under strong wind conditions is still an open theme of research investigations due to the limited lateral actuation available in the vehicle [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…Blimps are capable of staying still and aloft for years 54 and of providing a panoramic view in various directions with much convenience. With the use of latest photo or video editing technologies the concession may provide the park visitors with outstanding memories.…”
Section: Scenario One: Tethered Blimp 1 Model At a Scenic Overlookmentioning
confidence: 99%
“…In addition, UAS technology is on the verge of being integrated into hundreds of commercial and civil applications (Chamata 2017;LeMieux 2014), and will soon replace alternative technologies, i.e. helicopters, in various applications (Sebbane 2012). Recent advances have shown that UAS are extremely useful in benevolent activities such as search and rescue (Molina et al 2012), disaster management (Murphy et al 2008), and ambulancing (Daily Mail 2014).…”
Section: Introductionmentioning
confidence: 99%